Graphene Oxide Under the Nanoscope: A Comprehensive Study of Nanoindentation Behavior - Baltazar-Rojas, S; Rojas-Núñez, J (Elsevier Editora Ltda, 2024)
Graphene oxide membranes are expected to become one of the most important materials for technological applications due to their highly reactive surface, being directly related to their atomistic configuration. The understanding of its structure and physicochemical properties under mechanical deformation is becoming crucial in the development of new applications; however, the role of the different functional groups in the membrane and their response to external factors like indentation is still unclear. Nanoindentation experiments show elastic behavior when the penetration is small compared to the indenter radius and the membrane diameter. Molecular Dynamics simulations for large 3-layer graphene oxide membranes were carried out for a 50% oxidation content and the inclusion of epoxy and hydroxy groups. Simulations showed an elastic modulus similar to experimental values. After the elastic regime, the mechanical behavior is dominated by the evolution of functional groups. A quasi-elastic regime is uncovered, where unloading leads to self-healing of broken bonds. Finally, large indenter penetration leads to fracture, with fracture stress similar to experimental values. © 2024 The Authors